Information technology in next millennium - Shukla, Rajiv (New Delhi Rajat, 2000)
The concept information technology is a new one in the field of all types of technologies. The growth and development of information technology is one of the most significant achievements of the present century. The importance of information technology as
Keywords: Information technology; Technology